Masked Randomized Trial of Epinephrine versus Vasopressin in an Ovine Model of Perinatal Cardiac Arrest - Munmun Rawat; Sylvia Gugino; Carmon Koenigsknecht; Justin Helman; Lori Nielsen; Deepika Sankaran; Jayasree Nair; Praveen Chandrasekharan; Satyan Lakshminrusimha (Children, 2023)
Background: Current neonatal resuscitation guidelines recommend the use of epinephrine for bradycardia/arrest not responding to ventilation and chest compressions. Vasopressin is a systemic vasoconstrictor and is more effective than epinephrine in postnatal piglets with cardiac arrest. There are no studies comparing vasopressin with epinephrine in newly born animal models with cardiac arrest induced by umbilical cord occlusion. Objective: To compare the effect of epinephrine and vasopressin on the incidence and time to return of spontaneous circulation (ROSC), hemodynamics, plasma drug levels, and vasoreactivity in perinatal cardiac arrest. Design/Methods: Twenty-seven term fetal lambs in cardiac arrest induced by cord occlusion were instrumented and resuscitated following randomization to epinephrine or vasopressin through a low umbilical venous catheter. Results: Eight lambs achieved ROSC prior to medication. Epinephrine achieved ROSC in 7/10 lambs by 8 ± 2 min. Vasopressin achieved ROSC in 3/9 lambs by 13 ± 6 min. Plasma vasopressin levels in nonresponders were much lower than responders after the first dose. Vasopressin caused in vivo increased pulmonary blood flow and in vitro coronary vasoconstriction. Conclusions: Vasopressin resulted in lower incidence and longer time to ROSC compared to epinephrine in a perinatal model of cardiac arrest supporting the current recommendations for exclusive use of epinephrine in neonatal resuscitation.